Role of Home Care Nurses for Older Adults with End Stage Cancer - Utthiya, Pinyo (Journal of The Royal Thai Army Nurses, 2020)
Cancer is a globally critical problem in public health, due to it severity including the burden of this disease affecting life quality of patients and their families. When progressing to final stages of cancer, patients are suffered physically, mentally, emotionally, socially and spiritually. Their capability of self-care is decreased, especially in the elderly who appear to be more suffered, demanding more attention and care than other groups of patient. Caring elderly cancer patients at home induces anxiety and uncertainty to the family, effect to decrease QOL of patient and family. In order to provide continuous home care for elderly patients with terminal cancer and maintain their quality of life, that’s why home care nurses from Home Health Care Nursing takes the important role on this patient group starting from hospitalization until peacefully death including roles in planning for discharge, home visit, scheduled phone visit to offer care consult and refer to community health facilities. until their death with dignity, as well as to follow up with the family in handling the situation of loss after patient’s death. This article aims to role of home health care nurse for older adults with end stage cancer care at home.